Педагогическая практика как средство профессиональной подготовки студентов - Балгабаева, Г.З. (My University, 2013)
This article discussesthree waysmanagementresearch in theuniversity, depending on the characteristics ofthe individual student.Justconsiderthe use of varioustypesof educational research, design and research activitiesas a form ofresearch skills. The author considers that in the current context of growing dependency of the school's decision educational objectives of the professional competence of teachers. This requires improving the system of teacher training and continuous process of professional development specialist.